The Volatile Analogy of Premenstrual Disorders and Neglected Mental Health Care of Women: A Descriptive Study - Arsha Subbi, Dr. Balakrishnan Kalamullathil (International Journal of Advanced Science and Technology, 2020)
Background and Objectives: Several comprehensive studies on premenstrual troubles are now being conducted on a multidimensional scale incorporating biology and psychiatry. Ovulatory women experience anxiety and behavioral changes during the premenstrual period .This study purports to systematically evaluate the findings estimating the extent of psychological conditions faced by women during this period.Materials and Methods: Studies were identified using PubMed and MedInd, and Google Scholar databases. The two questionnaires prepared determined the extent of PMS, PMDD and PME among the study population. Pooled prevalence rate of the physiological and psychological symptoms were recorded.Results: In the current study including 100 study participants, 71% of subjects were identified as having PMS, 17% PMDD and 12% with PME. Further, the study showed 37 % of participants as having severe cramps, 34% experienced acute tiredness, 20% bloating and 9 % having headaches. The chronic psychological symptoms faced by the participants during this period were recorded as well. 56% of the study participants experienced irritability and anger before and during menstruation,17% felt depressed and sad, 16% were tearful and emotional and 11% felt overwhelmed and angst.Conclusions: Epidemiological correlations have been found between major psychotic disorders and premenstrual dysphoric disorders. Systemic efforts ought to be taken so as to address these concerns connecting menstruation and psychological disorders in women